Description of twelve new species of Platypalpus Macquart from Europe and the Middle East (Diptera, Empidoidea, Hybotidae) - Barták, Miroslav; Grootaert, Patrick (Zootaxa, 2024)
Twelve new species of Platypalpus Macquart from Europe and the Middle East are described, classified in three out of the eleven West-Palaearctic species groups. The albiseta group is represented by only one species: P. flavisetoides sp. nov. (Turkey). Two species belong to the longicornis group: P. curvifemur sp. nov. (Turkey) and P. vercorsensis sp. nov. (France). The pallidiventris-cursitans group is the most abundant group with nine species: P. exsectus sp. nov. (Bulgaria), P. huzur sp. nov. (Turkey, Greece), P. kayakoyensis sp. nov. (Turkey), P. kubiki sp. nov. (Spain), P. lorcaensis sp. nov. (Spain), P. sanrossorensis sp. nov. (Italy), P. serviae sp. nov. (Spain, Portugal), P. slovacus sp. nov. (Slovakia) and P. turgidoides sp. nov. (Spain).
Keywords: Animals; velikost těla; Europe; Female; Middle East; ženské pohlaví; Organ Size; Střední východ; anatomické struktury zvířat; Body Size; Evropa; Animal Distribution; Animal Structures; velikost orgánu; Male; Diptera; mužské pohlaví; zvířata; rozšíření zvířat